Cost Assessment of Utilizing Bagasse to Grow Sugarcane Based on Nutrient Availability - Jehangir H. Bhadha; Nan Xu; Naba R. Amgain; Abul Rabbany; Trent Blare; Fredy H. Ballen; Stewart Swanson (EDIS)
This new 7-page publication of the UF/IFAS Food and Resource Economics Department explores the potential of using bagasse, a dry and fibrous residue of sugarcane left after the sugar juice extraction, as a nutrient source to potentially reduce inorganic fertilizer inputs in the sugarcane production system. Information provided in this article will be useful to commercial sugarcane growers, crop consultants, and fertilizer manufacturers in helping them explore alternative fertilizer options. This paper provides important and timely information for the target audiences, considering the recent, rapid rise in fertilizer prices. Written by Jehangir H. Bhadha, Nan Xu, Naba R. Amgain, Abul Rabbany, Trent D. Blare, Fredy H. Ballen, and Stewart Swanson. https://edis.ifas.ufl.edu/fe1121